Gospodarka paszowa jako element kształtowania produkcji rolniczej - Szymańska, Elżbieta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
In the study, there was investigated the influence of increasing acquisitions of feeding stuffs on modelling the agricultural production. An analysis covered 92 farms divided into three groups according to the value of purchased feeding stuffs per 1 LU (big livestock unit). Research results show that jointly with the rise in the level of purchasing feeding stuffs, the size of fodder area per 1 LU has increased and the change in its structure was noticed. Extended purchases of feeding stuffs resulted in increasing costs of animal production but gave the opportunities to reach the higher level of agricultural production and income as well.